Advances in biotechnology for food industry - Holban, Alina Maria; Grumezescu, Alexandru Mihai (Handbook of food bioengineering ;, 2018)
Advances in Biotechnology for Food Industry, Volume Fourteen in the Handbook of Food Bioengineering series, provides recent insight into how biotechnology impacts the global food industry and describes how food needs are diverse, requiring the development of innovative biotechnological processes to ensure efficient food production worldwide. Many approaches were developed over the last 10 years to allow faster, easier production of widely used foods, food components and therapeutic food ingredients. This volume shows how biotechnological processes increase production and quality of food products, including the development of anti-biofilm materials to decrease microbial colonization in bioreactors and food processing facilities.--Resumé vydavatele